Acceptance and Use of Agree Mart App Using UTAUT-3 in Indonesia - Salman, Irfan Nurdin (Penerbit Goodwood, 2023)
Purpose: The use of applications for trade transactions in the digital era is increasingly in demand by the public, one of which is to meet their daily needs. There is no exception in the food sector to meet the needs of kitchens and fresh products, more and more applications are trying to meet these needs. However, the commodities that are sold are commodities that are quite vulnerable both in terms of price (price sensitive) and resilience (perishable goods). Instead of creating e-commerce groceries in the food sector, PT Telkom Indonesia prefers to create a grocery marketplace, so that it is not affected by price conditions and product durability because the products sold are owned by MSMEs. Research methodology: This research method uses a mixed method by taking a sample of the population of active users in Indonesia and using samples from several respondents, and registered users who have not made transactions Results: It is hoped that this research will provide benefits to add insight and as a digital business reference and material for consideration for meeting daily needs in Indonesia in determining the right strategy both in business and application. Conclusions: The research concludes that users’ intention to use Agree Mart is strongly influenced by how useful, easy, enjoyable, and cost-effective they perceive the app to be, as well as their existing habits and innovative tendencies. Behavioral intention is a critical predictor of actual usage, while external social influence and facilitating conditions have minimal impact on intention. However, facilitating conditions and habit do significantly influence use behavior. Limitations: This study is limited by its focus on respondents who have already made transactions using the Agree Mart application, which may exclude insights from potential users or those who have discontinued use. The research is also context-specific to Indonesian users, and findings may not be generalizable to other regions or cultural settings. Contribution: This study contributes to the growing body of knowledge on technology acceptance by applying and extending the Unified Theory of Acceptance and Use of Technology (UTAUT2) model to the context of an Indonesian groceries marketplace application, Agree Mart. It provides empirical evidence on the significance of performance expectancy, effort expectancy, hedonic motivation, price value, habit, and personal innovativeness in shaping users’ behavioral intentions.